Playful educational intervention with schoolchildren on intestinal parasitosis - Gabriela Rodrigues Bragagnollo; Tâmyssa Simões dos Santos; Renata Elizabete Pagotti da Fonseca; Marcelo Acrani; Maria Zita Pires Castelo Branco; Beatriz Rossetti Ferreira
ABSTRACT Objective: To analyze the playful educational interventions in the knowledge of schoolchildren about intestinal parasitosis. Method: This is a quasi-experimental, non-randomized study, based on pre- and post-intervention, conducted in a public elementary school in a peripheric neighborhood in the city of Ribeirão Preto (SP). The study population consisted of 101 students enrolled in the 5th and 6th grade. For comparison, we used the generalized version of the McNemar chi-squared test. Results: Of the 101 schoolchildren who participated in the study, 48 (47.5%) were female and 53 (52.5%) were male, aged from 9 to 14 years. Students' knowledge on intestinal parasitic infections has increased significantly after the playful educational intervention. Conclusion: Playful educational interventions are an excellent didactical resource in the teaching-learning process of schoolchildren.